2022
DOI: 10.1016/j.jaac.2021.08.023
|View full text |Cite
|
Sign up to set email alerts
|

Meta-analysis: Dose-Dependent Effects of Methylphenidate on Neurocognitive Functioning in Children With Attention-Deficit/Hyperactivity Disorder

Abstract: This is a PDF file of an article that has undergone enhancements after acceptance, such as the addition of a cover page and metadata, and formatting for readability, but it is not yet the definitive version of record. This version will undergo additional copyediting, typesetting and review before it is published in its final form, but we are providing this version to give early visibility of the article. Please note that, during the production process, errors may be discovered which could affect the content, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 79 publications
1
13
0
1
Order By: Relevance
“…c h i l d r e n a n d a d o l e s c e n t s w i t h A D H D Methylphenidate's effects have shown to be significant in terms of symptom reduction (e.g., Correll et al, 2021; Large effect size) and ER improvement by reducing overt and covert dysregulated behaviors (e.g., Pringshein et al, 2015; moderate to large effect sizes). When examining methylphenidate's effects on EFs as a unitary construct, they range from low to medium (e.g., Correll et al, 2021): Methylphenidate's effects on working memory updating producing a low effect size (e.g., , its effects on inhibitory control range from low to moderate with the majority producing a low effect size (e.g., Lee et al, 2022), and its effects on cognitive flexibility have been evaluated to be significant with a moderate effect size (e.g., Vertessen et al, 2021). Finally, methylphenidate's effects on QoL are significant with a marked improvement in QoL measures (Moderate to large effect sizes, e.g., Correll et al, 2021;Storebø et al, 2015;Tsujii et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…c h i l d r e n a n d a d o l e s c e n t s w i t h A D H D Methylphenidate's effects have shown to be significant in terms of symptom reduction (e.g., Correll et al, 2021; Large effect size) and ER improvement by reducing overt and covert dysregulated behaviors (e.g., Pringshein et al, 2015; moderate to large effect sizes). When examining methylphenidate's effects on EFs as a unitary construct, they range from low to medium (e.g., Correll et al, 2021): Methylphenidate's effects on working memory updating producing a low effect size (e.g., , its effects on inhibitory control range from low to moderate with the majority producing a low effect size (e.g., Lee et al, 2022), and its effects on cognitive flexibility have been evaluated to be significant with a moderate effect size (e.g., Vertessen et al, 2021). Finally, methylphenidate's effects on QoL are significant with a marked improvement in QoL measures (Moderate to large effect sizes, e.g., Correll et al, 2021;Storebø et al, 2015;Tsujii et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Recently, methylphenidate's effects on EFs in children and adolescents with ADHD have been evaluated in five systematic and meta-analytic reviews Lee et al, 2022;Mckenzie et al, 2022;Tamminga et al, 2016;Vertessen et al, 2021). These reviews included studies that in their vast majority, were double blind placebo controlled randomized trials with participants between the ages of 5 and 18 that examined, among other cognitive functions, working memory updating, inhibitory control, and cognitive flexibility.…”
Section: Methylphenidate and Executive Functionsmentioning
confidence: 99%
See 1 more Smart Citation
“…É importante que esse grupo populacional ao iniciar o uso de Metilfenidato tenham um acompanhamento e acesso direto aos profissionais de saúde na eminência de qualquer efeito adverso, uma vez, que a associação temporal direta indica que o medicamento poderia ser um potencial gatilho para desencadear infarto em pacientes com alguma predisposição 26. Infere-se que, é extremamente importante que a equipe multidisciplinar reconheça as etapas do processo de desenvolvimento infantil, principalmente no que se refere às mudanças corporais para que em conjunto com os familiares acompanhem seu desenvolvimento 25 . Orientação semelhante ao do estudo de revisão sistemática e meta-análise em que os dados destacam a importância de considerar os aspectos neurocognitivos e principalmente sintomáticos do TDAH na prática clínica 30 .…”
Section: Inapetência Perda De Peso Alopecia E Alterações Nos Parâmetr...unclassified
“…A primary purpose of attending school is to acquire skills such as reading and numerical operations and content knowledge in areas such as science and social studies. Many studies have shown that stimulants improve cognitive functioning on laboratory tasks (Coghill et al, 2014; Pietrzak et al, 2006; Rapport & Kelly, 1991; Swanson et al, 2011; Vertessen et al, 2021) and academic seatwork productivity in analog classrooms (Fabiano et al, 2007; Kortekaas-Rijlaarsdam et al, 2019; Pelham et al, 1985; Prasad et al, 2013). Children complete more seatwork and spend more time on task when medicated.…”
mentioning
confidence: 99%